Les différentes dimensions de la mémoire du séisme de 2010 en Haïti - Alice Corbet (L'Espace Politique)
The earthquake of January 12, 2010 hit the Haitian capital city of Port-au-Prince. Based on field anthropological research and studies in media archives, this article sheds light on the memory of the disaster and its dead. Doing so, it shows links between daily practices, official ceremonies and a political perspective of disregard between the State and the citizens. The literature mobilized ranges from newspapers factual notes on official ceremonies to academic work by specialist researchers, particularly on vodou, which is omnipresent in Haiti. Thus, this work puts into context the various dimensions of the memory of the 2010 earthquake, which oscillate between socio-cultural adaptations and more political dimensions. It shows that the relationships of power and domination in Haiti are reflected even in memory practices.The paper explains how the poorest dead have been often buried near the place of death or in mass graves. Families suffer from not knowing where the bodies of their loved ones are, because death was violent, sudden and collective. It is the practices and informal places of memory of the disappeared that are presented in the first part called “The scattered practices of memory in the heart of life and the city”. There are many places of “encounter” with the dead and death in general, notably thanks to vodou, in which there are intermediaries between the world of the living and the world “beyond”. These places can be material: one can go to cemeteries for example, and in particular near symbolic sites such as that the Cross of the vodou spirit “Baron Samdi”. There are also immaterial dimensions, very close to the previous ones, such as those where a living relative meets his deceased or the spirits through religious ceremonies. These different practices make it possible to remember, but also possibly to protect oneself from the dead who might be unhappy with their fate.In the second part, entitled “Materializing remembrance in the public space”, the article describes several memorials scattered throughout the city. They are often created on private initiative but are generally not accessible to a wide public, except the one in the park of the unsafe district of Martissant. The paper focuses on the evolution of the site of the main mass graves of Titanyen, north of the capital, which is emblematic because it includes a very large number of corpses and has been publicized in the media. Titanyen was quickly identified as the site of the “National Memorial” of the earthquake and was even officially renamed “Morne Saint Christophe”. But it is little frequented by the population, almost abandoned, and only invested by political representatives on the anniversaries of the disaster. Initially isolated, this memorial is still under construction and is increasingly surrounded by the giant post-earthquake slum of Canaan.The conclusion comes back to the historical non-accountability between the State and the Haitian population. The absence of a decent National Memorial embodied the fact that, even if the traces of the earthquake are still omnipresent, the numerous poor populations does not deserve to have a State recognition. The abandonment of the Titanyen site reflects the detachment and indifference of the rulers towards their citizens, who are already encountering many socio-economic difficulties linked to a State that has always forgotten the “outsiders” people. The tools of memory mobilized by people are therefore the usual cultural instruments, especially religious ones, drawn from the daily life of the inhabitants.